Multi-origin authigenic calcite controlled by the depositional environment and fluid−rock interactions in the Triassic siliciclastic strata, Junggar basin, NW China. (February 2023) - Hu, Ruipu; Kang, Xun; Tan, Jingqiang; Yan, Xiong; Dick, Jeffrey M.; Hu, Zhizhong; Wang, Wenhui
Abstract: Authigenic calcite records geologic fluid activities in sedimentary rocks, and its origin varies with changing sedimentary environments and fluid−rock interactions. This study investigated authigenic calcite with multiple origins in the Triassic siliciclastic strata of the petroliferous Mahu Sag, Junggar Basin, NW China. Detailed core logging was followed by lithological studies including optical, scanning electron and cathodoluminescence microscopic observations together with geochemical analyses of major elements and stable carbon and oxygen isotopes. The results show that there are three stages of calcite in the Baikouquan Formation with significantly differential MnO contents (average = 0.94%, 3.87%, 7.84%, respectively) and obviously negative δ 13 C values (−57.5‰ to −13.9‰, VPDB). It reflects the evaporation during deposition, and oxidation of hydrocarbon in oxidizing diagenetic environment. Extensive feldspar dissolution promotes the precipitation of late-stage calcite. There are two stages of calcite in the Karamay Formation and Baijiantan Formation. The positive correlation of their MgO and FeO contents reflects the alteration of volcanic materials in the strata. For the early-stage calcite, the low MnO contents (average = 0.50% and 0.61%) and positive δ 13 C values (>−10‰), demonstrate the paleo-meteoric water input. While the high MnO contents (average = 4.59%) and negative δ 13 C values (−25‰ to −10‰) of the late-stage calcite in the Karamay Formation indicate hydrocarbon charging and subsequent decarboxylation of organic acid, accompanied by feldspar dissolution. The late-stage recrystallization calcite of the Baijiatan Formation inherits the MnO and carbon isotopic characteristics of the early-stage calcite. This study shows that authigenic calcite is an effective recorder of sedimentary environment and fluid−rock interactions in siliciclastic strata. It enhances the heterogeneity of siliciclastic strata and is beneficial to hydrocarbon accumulation in lithological reservoirs. Highlights: Siliciclastic strata in a lacustrine transgressive systems tract underwent differential hydrocarbon charging intensity. Multiple calcite stages occur and exhibit differential MnO contents and stable carbon isotopic compositions. Hydrocarbons, organic acid, and paleo-meteoric water provided carbon sources for authigenic calcite. Different calcite stages and their geochemical signatures can indicate evolving fluid−rock interaction mechanisms.